Ibn Sina, Divine Simplicity and the Problem of Ineffability - Hossein Khodadadi (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
This paper explores applying the truthmaker theory to address the challenge of divine simplicity and its alignment with Ibn Sina’s understanding of divine attributes. It proposes that God’s essence enables the predication of these attributes, eliminating the need for constituent properties. By adopting this approach, meaningful statements about God can be expressed without delving into ontological intricacies. The truthmaker account establishes a direct connection between God’s necessary existence and the truthfulness of statements about Him, overcoming the barrier of ineffability. It offers a robust framework for understanding and expressing the truth of divine attributes while preserving divine simplicity. Ultimately, the truthmaker account provides a compelling resolution to the problem of ineffability in the realm of divine attributes in Ibn Sina’s philosophy.